IMPLEMENTATION OF REPETITION DEMONSTRATION TECHNIQUE TO IMPROVE MOTORCYCLE ENGINE OIL CHANGE ABILITY IN STUDENTS WITH MILD INTELLECTUAL DISABILITY (ATIKANOTO: Journal of Automotive Engineering Education, 2025)
This study aims to examine the effectiveness of the repetition-demonstration technique in improving motorcycle engine oil replacement skills among students with mild intellectual disabilities at SLBN A Citeureup Cimahi. The research method employed was a Single Subject Research (SSR) design with an A-B-A-B model to compare baseline and intervention conditions. The subject of the study was an 18-year-old student with mild intellectual disability. Data were collected through direct observation and practical tests, with the dependent variables including frequency, percentage, duration, latency, magnitude, trials, and rate. The results showed significant improvement in all aspects after the application of the repetition-demonstration technique. In the first baseline phase, the subject was only able to complete 25 out of 42 steps (59.5%) with a duration of 13–16 minutes. After the intervention, the subject demonstrated improved performance, completing 40–42 steps (95–100%) with greater efficiency in duration. Visual analysis of the graphs confirmed the effectiveness of this technique in enhancing independence and procedural accuracy. These findings support the use of repetition-based demonstration methods as an inclusive teaching strategy for vocational skills. Penelitian ini bertujuan untuk menguji efektivitas teknik repetisi demonstrasi dalam meningkatkan kemampuan penggantian oli engine sepeda motor pada peserta didik tunagrahita ringan di SLBN A Citeureup Cimahi. Metode yang digunakan adalah Desain Subjek Tunggal (Single Subject Research) dengan model A-B-A-B untuk membandingkan kondisi baseline dan intervensi. Subjek penelitian adalah seorang peserta didik tunagrahita ringan berusia 18 tahun. Data dikumpulkan melalui observasi langsung dan tes praktik, dengan variabel terikat meliputi frekuensi, persentase, durasi, latensi, magnitude, trial, dan rate. Hasil penelitian menunjukkan peningkatan signifikan pada semua aspek setelah penerapan teknik repetisi demonstrasi. Pada fase baseline 1, subjek hanya mampu menyelesaikan 25 dari 42 langkah (59,5%) dengan durasi 13–16 menit. Setelah diberi intervensi, subjek menunjukkan peningkatan kemampuan menjadi 40–42 langkah (95–100%) dengan durasi yang lebih efisien. Analisis visual grafik mengkonfirmasi efektivitas teknik ini dalam meningkatkan kemandirian dan ketepatan prosedur. Temuan ini mendukung penggunaan metode demonstrasi berbasis repetisi sebagai strategi pembelajaran inklusif untuk keterampilan vokasional.